Cl-doped carbon nitride nanostrips for remarkably improving visible-light photocatalytic hydrogen production. (13th August 2021) - Peng, Xinxin; Li, Junwei; Liu, Xi; Yi, Luocai; Cai, Pingwei; Wen, Zhenhai
Abstract: Visible-light-driven photocatalysts for hydrogen production have been made great progress in recent years, there yet remain grand spaces to be improved further for implementing practical feasibility. We herein report a chlorine doped carbon nitride (Cl-p-C3 N4 ) with ultrathin nanostrips morphology, which displays excellent photocatalytic hydrogen generation performance (5976 μmol h −1  g −1, 16.5 times higher than that of bulk C3 N4 ) under visible light irradiation, with an apparent quantum yield of 8.91% at 420 nm. Experimental results and DFT calculations show that the ultrathin Cl-p-C3 N4 nanostrips with heteroatom doping are greatly conducive to reduce the band gap, increase the surface area, and promote the separation efficiency of the photogenerated charge carrier, leading to the improvement of the charge carrier migration to the material surface or co-catalyst during the photocatalytic reaction. This work sheds light on the effective strategy to construct excellent photocatalyst by reasonably regulating the band structure and morphology. Highlights: Low-dimensional C3 N4 -based nanomaterials were successfully fabricated. Heteroatom doping is beneficial to the formation of broken nanosheets/nanostrips. The ultrathin Cl-p-C3 N4 nanostrips can provide abundant active sites. The ultrathin Cl-p-C3 N4 nanostrips display excellent photocatalytic activity.